IMPLEMENTATION OF LEGAL PROTECTION FOR VICTIMS OF SEXUAL VIOLENCE CRIMES (RESEARCH STUDY INTEGRATED SERVICE CENTER FOR WOMEN'S AND CHILDREN'S EMPOWERMENT IN THE CITY OF BANDA ACEH) - Fadillah Aditya Pratama; Ismaidar; Rahmayanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Children are a gift from God Almighty that we must always protect because in Him the dignity and rights inherent in the whole human being must be respected and protected. Child protection is a series of activities aimed at guaranteeing and protecting children and their rights so that children can live, grow, develop and participate optimally in accordance with their dignity, human rights, and are protected from violence and discrimination. As required by the 1945 Constitution of the Republic of Indonesia, Article 28B paragraph (2). Child protection activities are legal activities with legal consequences. Therefore, there is a need for legal protection efforts for child protection activities. This research focuses on how the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) in the city of Banda Aceh protects children's rights and the factors that hinder them. In this research, the research method that the author uses in this research uses empirical juridical methods and the author uses Observational Research methods. The data source for this research is analytical descriptive and comes from primary data from interviews with subjects and secondary data from books, journals, articles, theses, seminars and literature on the issues discussed in the Law. This research draws conclusions from general things to specific things. The conclusion from this research is that the efforts made by the government and the state to protect children who are victims of sexual violence are actually acceptable. However, there are several things that need to be considered in order to provide optimal protection to children as expected. Several factors that cause these difficulties include obstacles in the field which result in existing regulations appearing to be not as effective as expected.